Investigation and Evaluation of Potential Aerosol Release by Maquet/Getinge Heater–Cooler Units Used during Cardiac Surgery - Schwandtner, Sebastian; Reichel, Herwig; Jatzwauk, Lutz; Matschke, Klaus Ehrhard (The Thoracic and Cardiovascular Surgeon, 2019)
Background Heater–Cooler units (HCUs) supply tempered water through blood heat exchangers and through warming/cooling blankets to control the body temperature of heart surgery patients. Bacteria which potentially colonize the stored water may escape from the tank into the environment and are carried by the device's cooling air exhaust into the sterile field and finally may infect open chest heart surgery patients. Reports from several countries are connecting the infection of open chest heart surgery patients to airborne transmitted Mycobacteria chimaera which were found in the water of heater–cooler devices. As a consequence of the vigilance system for medical products, we investigated the potential release and the possible transmission of bacteria from the tank water into the sterile operating field.Materials and Methods In the absence of an evaluation standard for this problem, measurable acceptance criteria for particle releases and a qualitative method for bacteria transmission assessment have been deployed. To assess potential bacteria transmission into the sterile field, tank water of the test devices was inoculated with high concentrations of Pseudomonas aeruginosa (reference strain ATCC15442) and operated in an operating room with simulated use.Results The particle release at the tank lids of the Maquet/Getinge HCU 30 and HCU 40 during the filling of the tubes with water (deaeration) and during the removal of water from the tubes (emptying) increased slightly, but close to the blank readings for the larger particles. As expected, the particle release at the cooling air grids was higher than around the tank openings. Consistent with the particle measurements, no bacteria from the tank water were found in the sterile field during simulated use of all highly inoculated machines in an operating room.Conclusion In summary, we assess the risk of infecting open chest heart surgery patients with aerosol-transmitted bacteria from water inside the Maquet/Getinge HCU 40, HCU 30 to be negligible, if handled in accordance with common clinical hygienic precautions.
Keywords: infection; perfusion; practice; guidelines; surgery; complications; instruments